SCAPE: report on compliance validation - Ferreira, Miguel (2014)
This whitepaper describes the integrated technologies produced in SCAPE and the results of its assessment against the ISO 16363 – a framework for Audit and Certification of Trustworthy Digital Repositories. The work aims to demonstrate that a preservation ecosystem composed of building blocks as the ones developed in SCAPE is able to comply with most of the system-related requirements of the ISO 16363. The SCAPE Preservation Environment (SPE) is composed of a repository system, an execution environment, planning & watch services, preservation control policies, and best practice guidelines and reports. From a total of 108 metrics included in the ISO 16363, the SPE fully supports 69 of them. 31 metrics were considered to be “out of scope” as they refer to organisational issues that cannot be solved by technology alone nor can they be analysed outside the framework of a breathing organisation, leaving 2 metrics to be considered “partially supported” and 6 metrics to be considered “not supported”. This gives an overall compliancy level of roughly 90% (if the organisational oriented metrics are not taken into account). Even though we consider this to be an excellent result, proving and giving guidelines on how it would be possible to have a system compliant with most of the metrics included in ISO 16363, this also enabled us to identify the main weak points of the SCAPE Preservation Environment that should be addressed in the near future. In summary the gaps found were: The ability to manage and maintain contracts or deposit agreements through the repository user interfaces; Support for tracking intellectual property rights; Improve technical documentation, especially on the conversion of Submission Information Packages (SIP) into Archival Information Packages (AIP); The ability to aid the repository manager to perform better risk management. Our goal is to ensure that the SCAPE Preservation Environment fully supports the system-related metrics of the ISO 16363. In order to close the gaps encountered, additional features have been added to the roadmap of the SPE.